Demonstration of a multi-criteria based decision support framework for selecting PSS to increase resource efficiency - Michael Miller; Katharina Mattes (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2014)
One important aspect of sustainable societies is the efficient use of resources. The consideration of resource efficiency aspects when designing business models such as product service systems (PSS) allows incentivizing such efficiency increases in business relationships. Particularly PSS are able to increase resource efficiency by intensifying product use or decoupling volume from profitability by allowing the provider to participate in efficiency gains. Yet, the diffusion of PSS in resource-intensive industries is low, which can be explained in two ways: Firstly low awareness of the potential benefits of PSS on the customer side and secondly the lack of approaches from the customer perspective. The presented research therefore works out an approach to compare PSS as well as traditional business models from the customer perspective. A multi-criteria based decision support framework based on the method PROMETHEE is developed to support decision makers. The multi-criteria based decision support framework considers the benefits and perceived risks of introducing a PSS in a structured way to help potential customers evaluate the pros and cons of the selection of a specific PSS. The application of the multi-criteria based decision support framework simultaneously raises awareness for potential benefits of PSS. This publication demonstrates the use of the developed framework with possible PSS for supplying refractory linings at an electric arc furnace for steel production. The results discuss the advantages and disadvantages of the presented multi-criteria based decision support framework. The strengths of the methodology, implementing qualitative and quantitative criteria, avoiding scaling and compensation effects as well as the possibility to vary the preferences of the decision maker, facilitate the decision-making process.
urn:nbn:de:0011-n-3133315
Keywords: 330; PSS; material efficiency; energy efficiency; multi-criteria decision making; PROMETHEE; refractories